1991
DOI: 10.1017/s0033291700022327
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of cerebral activity underlying verbal fluency shown by split-dose single photon emission tomography (SPET or SPECT) in normal volunteers

Abstract: SYNOPSISUptake of 99mTc-Exametazime, a marker of relative regional cerebral blood flow has been determined with Single Photon Emission Tomography (SPET or SPECT) in 20 healthy, elderly female subjects during neuropsychological challenge. Each subject was studied under basal conditions after injection of 125 MBq 99mTc-Exametazime. Without moving the head of the subject, they were scanned again after injection of 375 MBq 99mTc-Exametazime. The second injection was made in 10 subjects during a test of verbal flue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Interestingly, patients with PSP or CBD may generate a small number of low-frequency words (eg, ‘peramubulator’) rather than high-frequency words (eg, ‘put’, ‘people’). This is supported by evidence from functional imaging suggesting that verbal fluency is associated with activation of a diffuse cortical network26 but with an emphasis on Brodmann area 45 for lexical retrieval and Brodmann area 46 in phonological processing during word generation 27. Patients with brain lesions in the left dorsolateral frontal lobe were found to have impaired verbal fluency if there were additional or solitary striatal lesions 28.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, patients with PSP or CBD may generate a small number of low-frequency words (eg, ‘peramubulator’) rather than high-frequency words (eg, ‘put’, ‘people’). This is supported by evidence from functional imaging suggesting that verbal fluency is associated with activation of a diffuse cortical network26 but with an emphasis on Brodmann area 45 for lexical retrieval and Brodmann area 46 in phonological processing during word generation 27. Patients with brain lesions in the left dorsolateral frontal lobe were found to have impaired verbal fluency if there were additional or solitary striatal lesions 28.…”
Section: Discussionmentioning
confidence: 84%
“…They also provided important evidence that frontal networks are active in performing ßuency in Alzheimer-type dementia just as they are in normals (Frith et al 1991). Interestingly, bilateral de-activation of temporal cortex seen in PET (Frith et al 1991) and SPET (Shedlack et al 1991) studies of normal subjects was not observed. A similar failure has also been observed in schizophrenic subjects and may, accordingly, be less speciÞc to that condition than was suggested .…”
Section: E¤ects On Brain Perfusionmentioning
confidence: 94%
“…Brain imaging is an important part of the diagnostic evaluation (1)(2)(3)(4). However, the brain image may be qualitatively difficult to distinguish between normal and demented persons, and more so between different dementia types such as AD and VD.…”
mentioning
confidence: 99%